From institutional communication management to cultural/heritage communication. RESTAURA (OHCH) as a case study. - Bueno Romero, Sandro; Villanueva Cabrera, Claudia; Dorticós Torriente, Yanet (Revista Universidad de Guayaquil, 2023)
How should a cultural service entity contribute, from effective institutional management to cultural/heritage communication, of the Historical Center/ Havana City Historian´s Office? These are some of the question/premises from which this research is based, which operates with the subsidiary company RESTAURA as a case study within the cultural/heritage management system of the HCHO, it is nurtured through techniques such as participant observation, qualitative interviews with experts and institutional agents, documentary/bibliographic analysis. This study aims to draw attention to those elements of cultural significance, which have to enrich the communicative management of RESTAURA, a budding process, in which a certain level of empiricism and spontaneity predominates, therefore not anchored sufficiently and holistically in processes systemic or scientific. Despite these dysfunctionalities at a communicative level, it has forged a high prestige in the face of projects and activities for the restoration of buildings of heritage value, in their surrounding socio-cultural context and other scenarios, including foreign ones. The apparent dissonance influences the systemic exercise of production of meanings favorable to knowledge, dissemination, legitimation and protection of the cultural assets of which RESTAURA is the manager. This investigative approach will be very useful in order to strategically plan, later, strengthen the communicational, cultural/heritage and media synergies, through which the processes of interaction between the actors and institutional/systems/structures/practices of the HCHO operate contributing to a responsible symbolic production through the reconstruction, rationalization, reproduction and legitimation of applied scientific knowledge.